Modelos de previsão para cheques compensados no Brasil - Carvalho, João José Melo de (2007)
The main objective of this dissertation was to develop a forecast model for the amount of compensated cheques in Brazil, aiming at its use as tool of bank politics for the maintenance of its efficient regulation, as anticipation of scenes of ways of payments and for strategical planning in financial institutions. Considering the cheque to be the basic instrument in this analysis, the statistic methodology of Time Series was used, specifically the exponential smoothing and the boarding of Box-Jenkins. The importance of the M1 (money supply) was also analyzed to study the reduction of the transactions with cheques in Brazil. The information used has been obtained from Bank of Brazil and IPEA and they relate to the monthly amounts compensated in the period between 1994 the 2005. The analyses have been carried through using MINITAB/EVIEWS (a computer programs) and several evaluated models of forecast, where the best result was using double exponential smoothing model and Holt- Winters models.